Fabrication of biocompatible alginate-poly(vinyl alcohol) nanofibers scaffolds for tissue engineering applications. (3rd July 2018) - Aadil, Keshaw R.; Nathani, Akash; Sharma, Chandra S.; Lenka, Nibedita; Gupta, Pratima
ABSTRACT: The present study signifies promising potential of alginate-poly(vinyl alcohol) nanofiber (ALPA- nf) in the field of tissue engineering. ALPA-nfs were fabricated by electrospinning using poly(vinyl alcohol) (PVA) blended with alginate in surfactant holding aqueous medium. Strong interaction between alginate and PVA resulted into improved physical properties, improving the stability of ALPA-nfs in the aqueous medium without any significant weight loss. The solubility and swelling percentage of ALPA nanofiber mat were found to be 32.23 ± 0.95 and 295 ± 4.2 respectively after 24 h. Visualization of microstructure by scanning electron microscopy (SEM) revealed the formation of random and smooth fibers. The consecutive interaction of alginate with PVA via hydrogen bonding was confirmed by FTIR analysis. Further, the biocompatibility study of ALPA-nfs revealed its non-cytotoxic impact on pluripotent embryonic stem cells (ESCs) in-vitro, facilitating their growth comparable to that seen under native condition, and hence its suitability as potent biomaterial scaffold. Graphical Abstract: